2011
DOI: 10.1007/s11845-011-0692-6
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus 16 or 18 infection and prostate cancer risk: a meta-analysis

Abstract: Even though the overall estimates did not provide a supportive evidence for the causal role of HPV in prostate carcinogenesis, higher HPV-16 DNA prevalence in PC cases from the stratified analysis still indicated a potential association between HPV infection and PC risk in our meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 45 publications
5
44
0
2
Order By: Relevance
“…HPV16 and 18 were most frequent HPV types in all cancers ranging from 50% to 84.7%. These findings are consistent to some epidemiological studies that had been reported HPV detection in variety of cancers (Syrjanen, 2002a;2002b;Iftner et al, 2003;Rezazadeh et al, 2009a;Tornesello et al, 2009;Li et al, 2011;Lin et al, 2011;Munoz et al, 2012;Simoes et al, 2012). However, detection of HPV DNA in these cancers by PCR alone is inadequate to verify causality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…HPV16 and 18 were most frequent HPV types in all cancers ranging from 50% to 84.7%. These findings are consistent to some epidemiological studies that had been reported HPV detection in variety of cancers (Syrjanen, 2002a;2002b;Iftner et al, 2003;Rezazadeh et al, 2009a;Tornesello et al, 2009;Li et al, 2011;Lin et al, 2011;Munoz et al, 2012;Simoes et al, 2012). However, detection of HPV DNA in these cancers by PCR alone is inadequate to verify causality.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, a number of non-malignant diseases such as genital warts and recurrent respiratory papillomatosis are attributable to HPV, particularly HPV6 and 11 (Chelimo et al, 2013;Gillison et al, 2012c). Moreover, HPV detected in several other cancers including esophageal squamous cell carcinoma (Syrjanen, 2002b;Tornesello et al, 2009), lung 1 * (Rezazadeh et al, 2009b;Munoz et al, 2012), prostate (Lin et al, 2011), ovarian (Rosa et al, 2013), breast (Simoes et al, 2012), skin (Iftner et al, 2003), colorectal (Burnett-Hartman et al, 2008;Lorenzon et al, 2011) and urinary tract cancers (Li et al, 2011), but association of HPV to these cancers is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, HPV may serve various roles in the development of cervical and PCa, and further high quality studies are required. In a meta-analysis study published in 2011, Lin et al (75) concluded that the causal role of HPV in prostate cancer remained doubtful, as the pooled results of DNA detection method and serologic assays (antibody) were negative; however, no statistical significance was observed in serological assays. The result was positive when the analysis was limited to HPV detection of type 16 infection in PCa tissues (75).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis study published in 2011, Lin et al (75) concluded that the causal role of HPV in prostate cancer remained doubtful, as the pooled results of DNA detection method and serologic assays (antibody) were negative; however, no statistical significance was observed in serological assays. The result was positive when the analysis was limited to HPV detection of type 16 infection in PCa tissues (75). Serological testing has the following limitations: i) Antibody cross-reactivity; ii) it is difficult to establish a temporal association between infection and cancer; iii) numerous individuals could be infected by HPV throughout their lifetime, so the control group may be positive; iv) based on a number of etiological studies, it is commonly agreed that HPV does not induce a generalized viremia; and v) only persistent infections induce pathological alterations and serological detection indicates HPV exposure rather than the exact site of infection (76).…”
Section: Discussionmentioning
confidence: 99%
“…The association between HPV and cancer of the prostate is discussed e.g. by Dodd et al [1993], Martinez-Fierro et al [2010] as well as by Lin et al [2011].…”
Section: Discussionmentioning
confidence: 99%